Inovasi Pembelajaran Sentra Religi Muslim Berbasis Pendekatan Saintifik Di TK Golden Kids Pandaan - Siti Tri Nuril Rokhima (4, 2025)
This research was conducted to determine the implementation and innovation of a scientific approach to Muslim religious center learning at Golden Kids Pandaan Kindergarten. In early childhood education, innovative learning approaches are essential for developing children's character from an early age. The scientific approach was chosen because it stimulates critical, active, and systematic thinking processes appropriate to the child's developmental stage. The purpose of this study was to determine the extent to which the scientific approach can be applied to the learning process at Golden Kids Kindergarten and to determine its impact on increasing learning interest and developing the spiritual character of young children. This study used a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The observed learning process included the five steps of the scientific approach: observing, asking questions, gathering information, reasoning, and communicating. The subjects were teachers and students in the Golden Kids Pandaan Kindergarten classroom. The results showed that the application of the scientific approach to Muslim religious center learning had a positive impact on the children. Children became more active in asking questions, were more involved in direct learning activities, and demonstrated a better understanding of religious values. Furthermore, teachers are becoming more creative in developing fun and meaningful learning activities. This innovation has been proven to shape children's spiritual character from an early age, making learning more engaging and developmentally appropriate. Abstrak Penelitian ini dilaksanakan untuk mengetahui bagaimana pelaksanaan dan inovasi pembelajaran sentra religi muslim dengan pendekatan saintifik di TK Golden Kids Pandaan. Dalam dunia pendidikan anak usia dini, pendekatan pembelajaran yang inovatif sangat dibutuhkan untuk membangun karakter anak sejak dini. Pendekatan saintifik dipilih karena mampu merangsang proses berpikir kritis, aktif, dan sistematis sesuai tahap perkembangan anak. Tujuan dari penelitian ini adalah untuk mengetahui sejauh mana pendekatan saintifik dalam sentra religi muslim dapat diterapkan dalam proses pembelajaran di TK Golden Kids, serta mengetahui dampaknya terhadap peningkatan minat belajar dan perkembangan karakter spiritual anak-anak usia dini. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Proses pembelajaran yang diamati meliputi lima langkah pendekatan saintifik yaitu mengamati, menanya, mengumpulkan informasi, menalar, dan mengomunikasikan. Subjek penelitian adalah guru dan siswa di kelas TK Golden Kids Pandaan. Hasil penelitian menunjukkan bahwa penerapan pendekatan saintifik dalam pembelajaran sentra religi muslim memberikan dampak positif terhadap anak-anak. Anak menjadi lebih aktif bertanya, terlibat dalam kegiatan pembelajaran secara langsung, dan menunjukkan pemahaman yang lebih baik terhadap nilai-nilai keagamaan. Selain itu, guru juga lebih kreatif dalam mengembangkan kegiatan belajar yang menyenangkan dan bermakna. Inovasi ini terbukti mampu membentuk karakter spiritual anak sejak dini, menjadikan pembelajaran lebih menarik dan sesuai dengan perkembangan anak usia dini